Workers' protection : the case of Trinidad and Tobago - Moonilal, Roodal (ILO Caribbean Office Port of SpainTT, 2001)
Presents an analyzes of the status of worker protection in Trinidad and Tobago. Describes the main situations in which workers lack sufficient protection and identifies the problem areas occasioned by a lack of insufficient protection for workers. Places particular emphasis on the legal and procedural avenues for worker protection, representation and redress of selected categories of workers in the labour market.